PUBERPHONIA: A NOVEL APPROACH FOR TREATMENT - DR.D.SRIDHARA NARAYANAN,; DR.M. PRAKASH,; DR.VIBINA NARAYAN,; DR.HARIPRASAD,; MR.IYAPPAN, (International Journal of Pharma and Bio Sciences, 2014)
Puberphonia is inappropriate use of high pitched voice beyond pubertral age in males. Manifestation is less in women than men. Voice therapy is one of the modality of treatment. This study is to evaluate the efficacy of voice therapy in treatment approach of puberphonia and to document the effect of voice therapy on improvement of the quality of life of the patient. A Prospective study of twenty five cases with puberphonia. All cases were managed with various techniques of voice therapy. The subjective assessment of pre-voice therapy was done using GRBAS scale and objective assessment was done by acoustic analyses of vocal quality using Praat software. The psychosocial impact of puberphonia was assessed with the voice handicap index (VHI).All the twenty five patients achieved appropriate pitch range following voice therapy. All scores of the Voice Handicap Index of all patients showed significant improvements.The study concludes that voice therapy has proven to be one of the most effective in the management of puberphonia. The study showed that the voice therapy not only improves the voice quality of the patients , but also improves the quality of life of the patient.